Is Utena's Brief Objective Measures (UBOM) useful in real‐world behavioral assessment of functioning? Validity and utility testing in patients with schizophrenia. Issue 1 (10th October 2019) - Sawada, Kingo; Sakakibara, Eisuke; Kanehara, Akiko; Koike, Haruna; Suga, Motomu; Fujieda, Yumiko; Miyamoto, Yuki; Fukuda, Masato; Kasai, Kiyoto
Abstract : Aim: Utena's Brief Objective Measures (UBOM) was developed to assess psychophysiological functions proximal to real‐world functioning in individuals with psychiatric disorders, including schizophrenia (SCZ), to facilitate shared decision‐making. However, the validity of UBOM has not been fully examined. Methods: We conducted a cross‐sectional observational study to evaluate the validity of each of the three tests in UBOM: UBOM‐Pulse, UBOM‐Ruler, and UBOM‐Random. We investigated associations: (i) between UBOM and existing cognitive‐ and autonomic‐function tests; and (ii) between UBOM and daily social functioning. The participants included SCZ individuals and healthy controls. We evaluated the cognitive and autonomic function using UBOM, the heart rate variability test, the simple reaction time test, and the Brief Assessment of Cognition in Schizophrenia, Japanese version. We also assessed the daily social functioning using the WHO Disability Assessment Schedule 2.0 and the modified Global Assessment of Functioning, Japanese version. Results: Thirty‐one SCZ individuals and 35 healthy control individuals participated in this study. In the SCZ group, UBOM‐Ruler was significantly associated with the Cognition and Getting Along domains of WHO Disability Assessment Schedule 2.0. UBOM‐Random was significantly associated with the Brief Assessment of Cognition in Schizophrenia's Working Memory, Verbal Fluency and Attention domains, and the modified Global Assessment of Functioning in the SCZ group. Conclusion: The validity of the current version of UBOM is imperfect and further improvements will be necessary to attain the originally intended goal of developing a brief assessment tool for real‐world functioning in SCZ.